Foreign Direct Investment and Trade Components in Context of Pakistan - Gilal, Muhammad Akram; Hussain, Khadim; Ajmair, Muhammad; Akram, Sabahat (European Scientific Journal, ESJ, 2016)
Objective of this paper was to evaluate the impact of foreign direct investment (FDI) on trade components (exports and imports) of Pakistan using annual data from 1975 to 2013. Engle and Granger two step cointegration method was used for conducting the analysis. This method was adopted because all the variables of interest were non stationary in level and stationary at first difference. Results provide evidence of long run cointegrating relationship as well as short run relationship between FDI and trade components. A rise in FDI causes both exports and imports to increase. Based on these empirical findings, we strongly recommend Government of Pakistan to focus on the strategy of investment liberalization as well as trade openness.